2005
DOI: 10.1111/j.1462-2920.2005.00795.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel predominant archaeal and bacterial groups revealed by molecular analysis of an anaerobic sludge digester

Abstract: A culture-independent molecular phylogenetic approach was used to study prokaryotic diversity in an anaerobic sludge digester. Two 16S rRNA gene libraries were constructed using total genomic DNA, and amplified by polymerase chain reaction (PCR) using primers specific for archaeal or bacterial domains. Phylogenetic analysis of 246 and 579 almost full-length 16S rRNA genes for Archaea and Bacteria, respectively, was performed using the ARB software package. Phylogenetic groups affiliated with the Archaea belong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
163
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 267 publications
(181 citation statements)
references
References 59 publications
10
163
2
1
Order By: Relevance
“…Approximately 51% and 21% of the clones analyzed for reactors 1 and 2, respectively, were closely related to uncultured archaeal 16S rRNA gene clones that were not targeted by our probe set (Figure 3). In addition to these uncultured methanogen-like groups, it is known that clones assigned to the candidate taxon WSA2 of the Euryarchaeota and the subphylum C2 of the Crenarchaeota have been retrieved from some methanogenic sludges in abundance (Chouari et al, 2005;Collins et al, 2005), although the archaeal rRNA gene cloning analysis for the sludges in this study showed no detection of such phylotypes. Thus there is a further need to develop additional scissor probes to cover these uncultured Archaea to better determine the abundance of the archaeal populations in natural and engineered environments in the future.…”
Section: Discussionmentioning
confidence: 48%
“…Approximately 51% and 21% of the clones analyzed for reactors 1 and 2, respectively, were closely related to uncultured archaeal 16S rRNA gene clones that were not targeted by our probe set (Figure 3). In addition to these uncultured methanogen-like groups, it is known that clones assigned to the candidate taxon WSA2 of the Euryarchaeota and the subphylum C2 of the Crenarchaeota have been retrieved from some methanogenic sludges in abundance (Chouari et al, 2005;Collins et al, 2005), although the archaeal rRNA gene cloning analysis for the sludges in this study showed no detection of such phylotypes. Thus there is a further need to develop additional scissor probes to cover these uncultured Archaea to better determine the abundance of the archaeal populations in natural and engineered environments in the future.…”
Section: Discussionmentioning
confidence: 48%
“…It is likely that these groups were responsible for the apparent psychrophilic propionotrophic activity shown by batch activity assays (day 1243; Table 2). The Chloroflexi are reported to be important community members within mesophilic and thermophilic wastewater treatment systems, where they may represent up to 20% of the total microbiota (Chouari et al, 2005;Levén et al, 2007). Yet, few reports exist that describe their importance within cold environments.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term, low-temperature cultivation of mesophilic anaerobic sludge RM McKeown et al Crenarchaeota-like clones (Group 1.3) has been reported in both mesophilic (Chouari et al, 2005;Levén et al, 2007) and psychrophilically cultivated anaerobic granular biomass, where they may represent a significant proportion of the total archaeal microbiota McHugh et al, 2005). No Crenarchaeota-like ribotypes were detected at the conclusion of the trial (Figure 2e), which is in accordance with the findings of McHugh et al (2004) and Enright et al (2007), who reported the disappearance of Crenarchaeota-like clones during low-temperature wastewater treatment trials.…”
Section: Discussionmentioning
confidence: 99%
“…(Maidak et al, 1994); an 'in-house' database with sequences obtained from anaerobic digesters (Chouari et al, 2003(Chouari et al, , 2005aGuermazi et al, 2008).…”
Section: Sequence Analysismentioning
confidence: 99%
“…Our knowledge about the microbial consortia involved in this process is limited because of a lack of phylogenetic and metabolic data on these predominantly uncultivated microorganisms. As an alternative to culture techniques, several molecular inventories, based on the study of the 16S rRNA gene, were carried out on anaerobic environments and have shown the extent of the diversity in these complex ecosystems (Godon et al, 1997a, b;Sekiguchi et al, 1998;Leclerc et al, 2004;Chouari et al, 2005a). These studies have limitations in that they often focused on one type of process, one sample, and often only lab-scale units.…”
Section: Introductionmentioning
confidence: 99%